MOTIVASI SISWA MUSLIM SEKOLAH DI SMA SANTA MARIA KOTA PEKANBARU - Kesabarenta Ginting; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at the Santa Maria High School in Pekanbaru City whose object of research was Moslem students and parents who chose schools at the Santa Maria High School in Pekanbaru City. This study aims to see and know what motivates students and parents to choose to go to school with religious nuances that are different from the religion adopted. This study uses qualitative methods, namely the efforts made by working with data, organizing data, sorting it into units that can be managed by finding and finding patterns, also finding what is important and what is learned, and deciding what can later be told to other people. in this study there were 8 (eight) subjects who in the school there were only 4 (four) Moslem students who attended the school and therefore the researchers also examined 4 (four) parents of these students as subjects. The results of this study state that Moslem students motivated to continue their education in Catholic nuances schools are due to the quality possessed by schools, as well as parents who want their children to be disciplined and smarter, with which they choose the school of Santa Maria as a place to seek knowledge. This is based on self-decision, interest in talent, and their ideals are also based on encouragement from parents.